An enquiry into impact of HR architecture on human capital pool / Jyotirmayee Choudhury, Suresh Ch. Nayak and Noorlalia Hj Yunus - Choudhury, Jyotirmayee; Nayak, Suresh Ch; Hj Yunus, Noorlalia (University Publication Centre (UPENA) and Institute of Business Excellence, 2011)
The purpose of this research-which yielded more than 466 respondents-was to identify the idiosyncratic context of HR practices and policies followed by various IT organisations to strengthen their human capital pool. The research is carried out primarily on the basis of field survey and designed to study and analyse the extent to which HR practices and procedure practised in various Indian IT organisations are boosting development of human capital of that particular industry and found that both acquisition and developmental HR configuration has significant contributions for the development of the human capital of the organisations under study.